Analisis strategi email marketing dalam komunikasi pemasaran digital: studi kasus Traveloka - Agustina Riska Eka Saputri; Daniel Handoko; Makroen Sanjaya (Universitas Garut, 2026)
Abstract This study addresses a key issue in digital marketing communication practices, namely the growing tendency of email marketing to shift into a transactional and purely promotion oriented medium. This condition may lead to message fatigue, declining audience engagement, and the weakening of brand trust in the long term. In the context of increasingly intense competition within the digital industry, email marketing should not only function as a promotional channel but also as a relational communication medium capable of fostering sustainable relationships between brands and their audiences. Therefore, this study aims to analyze the email marketing strategies implemented by Traveloka by examining their communicative functions, message delivery patterns, forms of personalization, and the communication challenges that emerge in practice. This research employs a qualitative approach using a case study method through content analysis of Traveloka’s marketing emails, supported by a review of relevant literature on email marketing, relational communication, and trust in digital marketing. The findings indicate that Traveloka’s email marketing has been integrated into the company’s digital ecosystem and is effective in supporting transaction processes, service reminders, and product promotions. However, the dominance of promotional messages, personalization that remains largely technical and less contextual, as well as a high sending frequency, have implications for decreased audience engagement and emerging indications of trust issues. The contribution of this study lies in strengthening a communication perspective in evaluating email marketing, emphasizing that strategic success should not be measured solely by conversion and return on investment (ROI), but also by relationship quality, message relevance, and the long-term communicative value between brands and audiences. Keywords: Digital marketing communication; email marketing; marketing strategy; traveloka. Abstrak Penelitian ini berangkat dari isu utama dalam praktik komunikasi pemasaran digital, yaitu kecenderungan email marketing yang semakin bergeser menjadi media komunikasi yang bersifat transaksional dan berorientasi promosi semata. Kondisi tersebut berpotensi menimbulkan kejenuhan pesan (message fatigue), penurunan keterlibatan audiens (engagement), serta melemahnya kepercayaan (trust) terhadap merek dalam jangka panjang. Dalam konteks persaingan industri digital yang semakin ketat, email marketing seharusnya tidak hanya berfungsi sebagai saluran promosi, tetapi juga sebagai media komunikasi relasional yang mampu membangun hubungan berkelanjutan antara merek dan audiens. Oleh karena itu, studi ini bertujuan untuk menganalisis strategi email marketing yang diterapkan oleh Traveloka dengan meninjau fungsi komunikatif, pola penyampaian pesan, bentuk personalisasi, serta tantangan komunikasi yang muncul dalam implementasinya. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus melalui analisis konten terhadap email pemasaran Traveloka yang dikaitkan dengan kajian literatur mengenai email marketing, komunikasi relasional, dan trust dalam pemasaran digital. Hasil penelitian menunjukkan bahwa email marketing Traveloka telah terintegrasi dalam ekosistem digital perusahaan dan efektif dalam mendukung proses transaksi, pengingat layanan, serta promosi produk. Namun, dominasi pesan promosi, personalisasi yang masih bersifat teknis dan kurang kontekstual, serta intensitas pengiriman yang tinggi berimplikasi pada turunnya engagement audiens dan munculnya indikasi trust issue. Kontribusi penelitian ini terletak pada penguatan perspektif komunikasi dalam evaluasi email marketing, dengan menegaskan bahwa keberhasilan strategi tidak hanya diukur melalui konversi dan ROI, tetapi juga melalui kualitas relasi, relevansi pesan, serta nilai komunikasi jangka panjang antara merek dan audiens. Kata-kata Kunci: Komunikasi pemasaran digital; email marketing; strategi marketing; traveloka.